A Work study on Dynaflex Plastic Manufacturing Corporation - Dee, Allan B. (College of Engineering, 1997)
Methods Engineering is the branch of study of Industrial Engineering that is concerned with the design and measurement of work. One of the most powerful tool used in this area is the work study. A work study is the systematic examination of the methods of carrying on activities so as to improve the effective use of resources and to set up standards of performance for the activities being carried out. It aims at critically examining the methods in which an activity is being carried out, and then simplify or modify the operation so as to reduce unnecessary and excess work, or the wasteful use of resources. This work study is conducted in Dynaflex Plastic Manufacturing Corporation, a small plastic recycling plant in Valenzuela. During the course of the work study, the methods used in different areas of the production line were documented and analyzed to see if any improvements may be made. Other facets of production were also observed such as receiving procedures and paperwork flow. This paper is the result of the study that was conducted in five months' time. It addresses many issues regarding the operation of the plant. Some areas were not sufficiently covered but are addressed for further study since they are beyond the scope of this one. Hopefully, the recommendations made by this paper can be used effectively for the improvement of productivity in the operations of Dynaflex Plastic Manufacturing Corporation.